Cheating in online exams at Australian universities - E, Smith,; L, Clarke,; P, Carmona, (IJRDO- Journal of Educational Research, 2017)
In recent years an ever increasing number of universities have started to offer online degrees.In Australia most universities offer online degrees, however, this study will take a closer lookat an organisation which offers the largest selection of online courses. For the purposed of thisstudy the organisation will be referred to as “online degree providers” (ODP).Along with this new method of completing degrees comes new forms of academic dishonestyand misconduct. Academic dishonesty and misconduct among students is not a newphenomenon.As universities around Australia and the world are offering an increasing number of coursesand degrees online, it is important to plan how to deal with the problem of academic dishonestyand misconduct. In 1990, the American Council on Higher Education reported that cheating atwas on the rise at universities in the United States (US). In recent years, there has been a greatdeal of research in the area of academic dishonesty, most of which almost exclusively focusedon the US.This research considers academic dishonesty broadly, the focus of the paper is on cheating inonline exams. Other sorts of academic dishonesty, for example plagiarism or employingassignment-writing companies, are beyond the scope of this paper. With many courses usingan end-of-subject exam for up to 60% of the student's overall mark for the subject, it is vitallyimportant that cheating in exams be addressed.This paper contributes to the limited research literature on academic dishonesty and misconductin online programs and online exams at Australian universities by taking a close look at whatacademic dishonesty and misconduct is and how it is happening. It is important that thesequestions be understood because, students who cheat at university are more likely to becomeprofessionals who in the future will engage in illegal, unethical or immoral behaviours in theworkplace.